21.04: Vibration characteristics of an existing high‐rise building in Montreal and the effects of retrofit. (13th September 2017) - Manolache, Laura; Wang, Yudong; Tirca, Lucia; Bagchi, Ashutosh
ABSTRACT: The study described in this paper refers to seismic assessment and retrofit of an existing 10‐storey reinforced concrete office building designed and built at the beginning of the 20 century. When this building with a height of 38.95 m was completed it was the highest in downtown Montreal. According to FEMA 547 classification, the typology of this building structure is associated to model building type "C3". Consequently, this type of non‐ductile frame building with an insignificant amount of masonry walls is relatively weak and unable to carry the seismic forces when subjected to ground motions from a potential earthquake magnitude. The main deficiencies of this structural system are: poor lateral confinement and shear resistance of columns, the location of lap splices and the number of reinforcing bars often inadequate, the lack of confinement and shear reinforcement in joints, poor anchorage of longitudinal reinforcement of beams into joints and shear resistance of beams. Due to lack of seismic detailing, the common retrofit measure recommended in ASCE/SEI 41–13 for this building is to add new lateral force‐resisting systems designed according to current code and standard provisions. Hence, in this case, the most cost‐effective retrofit solution is to add a steel structure designed to withstand seismic forces while responding to serviceability criteria required to preserve the non‐reinforced masonry facades facing the main streets and the facades ornaments.